The Fucík spectrum for nonlocal BVP with Sturm–Liouville boundary condition - Sergejeva, Natalija (Nonlinear Analysis: Modelling and Control, 2014)
Boundary value problem of the form x’’=-μx++λx-, αx(0)+(1-α)x’(0)=0, ∫01 x(s)ds=0 is considered, where μ,λ∈ R and α∈ [0,1]. The explicit formulas for the spectrum of this problem are given and the spectra for some α values are constructed. Special attention is paid to the spectrum behavior at the points close to the coordinate origin.